Pencegahan Perundungan Anak Melalui Dukungan Sistem Sekolah Swasta pada Tingkat Sekolah Dasar - Tambunan, Alice Risma; Hermanto, Yanto Paulus; Deak, Victor; Yanto Paulus (Jurnal Teologi Praktika, 2025)
Prevention of Bullying Through the Support System of Private Elementary Schools. This study examines the relationship between bullying behavior and school support systems, including the application of Christian values, in private elementary schools. Using a mixed methods approach, data were collected from 334 respondents through questionnaires, interviews, and observations in three schools in Bogor and Jakarta. Quantitative results showed weak or non-significant correlations between bullying, support systems, and Christian values. However, qualitative findings revealed that structured support—such as counseling services, teacher involvement, anonymous reporting, and daily spiritual routines—plays a key role in creating a safe environment. The integration of values such as love, justice, and forgiveness through daily school activities strengthens students’ positive character. The study concludes that while measurable statistical impact may be limited, consistent implementation of character-building and faith-based programs contributes significantly to bullying prevention. Continuous monitoring and evaluation are recommended to sustain effective support systems.